Ecuaciones con 2 variablesVersion en ligne Sustitución de valores par Julio Arreola 1 7x + 5y = 80 a (10, 2) b (0, -9) c (6, 8) d (-1, 9) 2 9x + 3y = 33 a (2, -4) b (5, -4) c (7, -4) d (-7, -8) 3 3x + 3y = 51 a (-5, -1) b (6, -3) c (10, 7) d (6, 6) 4 7x + 3y = -43 a (-5, 7) b (7, 2) c (2, -2) d (-4, -5) 5 6x + 2y = -48 a (-6, -6) b (6, -6) c (-9, 2) d (-5, -3) 6 7x + 9y = -160 a (-5, 2) b (-10, -10) c (9, -6) d (5, -10) 7 7x + 6y = -118 a (1, -8) b (-2, 1) c (-10, -8) d (-9, 1) 8 8x + 8y = -80 a (10, -2) b (7, -7) c (-8, 8) d (-9, -1) 9 9x + 3y = -99 a (-8, -9) b (-10, -2) c (0, 2) d (-10, -1) 10 3x + 6y = -39 a (-2, -6) b (1, -7) c (5, -5) d (-8, -10) 11 5x + 9y = -81 a (3, 1) b (9, -5) c (0, -9) d (-8, -6) 12 4x + 7y = 53 a (8, -6) b (0, 10) c (6, -3) d (8, 3) 13 3x + 7y = -66 a (-8, -6) b (2, 4) c (7, -2) d (-7, 5) 14 8x + 5y = -45 a (-7, 10) b (0, -9) c (6, 10) d (2, 5) 15 6x + 2y = 64 a (-1, -4) b (4, 6) c (10, 2) d (-10, -10) 16 5x + 7y = 55 a (-5, 1) b (-6, -9) c (-10, 4) d (4, 5) 17 2x + 4y = 22 a (-7, 9) b (-5, 5) c (-9, -10) d (6, 9) 18 3x + 8y = -98 a (0, 10) b (-6, -10) c (6, -7) d (2, 5) 19 4x + 2y = -8 a (2, 8) b (7, -4) c (1, -6) d (9, -9) 20 4x + 5y = -67 a (-7, -8) b (10, 1) c (-2, 2) d (-8, -7) 21 4x + 5y = 80 a (10, 8) b (-4, -1) c (1, -10) d (-4, -7) 22 5x + 8y = 12 a (-6, 3) b (4, -1) c (-7, 10) d (-4, -1) 23 5x + 7y = -55 a (1, -7) b (5, 2) c (3, -10) d (-9, -7) 24 8x + 4y = -32 a (-10, 6) b (8, -9) c (-2, 7) d (-9, 10) 25 8x + 2y = 44 a (4, 6) b (-1, 9) c (10, 8) d (8, 3) 26 8x + 9y = 17 a (3, -8) b (-8, 9) c (-8, -2) d (-6, -2) 27 9x + 7y = 111 a (-7, -9) b (3, -1) c (10, 3) d (8, -7) 28 2x + 2y = -2 a (-4, -1) b (6, -5) c (4, 5) d (-9, 8) 29 6x + 4y = 6 a (-5, 9) b (2, 7) c (7, -1) d (7, 1) 30 8x + 2y = -78 a (10, 4) b (-9, -3) c (4, 1) d (7, 4) 31 4x + 9y = 25 a (5, -7) b (-1, 6) c (-5, 5) d (8, -8) 32 4x + 9y = -42 a (0, -6) b (2, 3) c (-6, 5) d (-6, -2) 33 5x + 5y = -70 a (-5, -9) b (-10, -5) c (2, -5) d (8, -5) 34 5x + 2y = -27 a (4, 5) b (-3, -6) c (-1, -2) d (5, -9) 35 5x + 6y = -104 a (-1, 7) b (-5, 1) c (-10, -9) d (-2, -7) 36 8x + 3y = 28 a (-6, -2) b (1, 8) c (-1, 0) d (2, 4) 37 4x + 6y = 38 a (2, 5) b (1, 7) c (-6, 7) d (5, 4) 38 7x + 3y = 45 a (0, -1) b (9, -6) c (-2, 10) d (9, -4) 39 5x + 3y = 53 a (7, 2) b (-7, 7) c (10, 1) d (-6, -1) 40 5x + 2y = 15 a (-6, -6) b (-8, -10) c (-2, -4) d (3, 0)